Knowledge and Attitude towards Probiotics among Dental Students and Teachers: A Cross-Sectional Survey - Ksenia Babina; Dilara Salikhova; Maria Polyakova; Alexandr Zaytsev; Anna Egiazaryan; Nina Novozhilova (MDPI AG, 2023)
This cross-sectional survey assessed the knowledge of and the attitude towards probiotics of dental students and academics at Sechenov University, Moscow, Russia. Our questionnaire consisted of 15 questions divided into 3 sections: respondents' sociodemographic data, knowledge on probiotics, and attitude towards probiotics. The data were analyzed using the Mann-Whitney U test, Fisher's exact test, and Spearman's rank correlation coefficient. Out of the 658 questionnaires distributed, a total of 239 questionnaires were completed by the undergraduates, yielding a response rate of 39.6%, and 54 by the teaching staff (response rate = 100%). Most students (53.6%) and teachers (55.5%) had a fair knowledge of probiotics (p = 0.3135). A vast majority of dental students (97.9%) and all teachers had a positive attitude towards probiotics, with higher mean scores among academics (p < 0.001). A positive weak correlation was found between knowledge and attitude (Spearman r = 0.17, p = 0.0027). The results obtained reveal the need for more evidence-based educational trainings for university teachers and a course on probiotics to be included in the curriculum for dental students.